Investigating Organizational and Human Resource Capacity of Village Government: A Case Study in Kutai Kartanegara Regency - Andi Wahyudi; Dewi Sartika; Fani Heru Wismono; Lany Erinda Ramdhani; Lia Rosliana; Mayahayati Kusumaningrum; Siti Zakiyah (Indonesian Association for Public Administration, 2020)
Indonesian Village Law No. 6/2014 mandates village to be a self-governing community and local self-government. Based on the law, village government conducts governmental administrative business, local development, fostering village societal, and empowering local people. To support the tasks, it is allowed to raise funds from various sources. This paper aims to investigate any problem and possible solutions to strengthen village capacity in order to achieve the village law vision. This research was conducted in Kutai Kartanegara (Kukar) Regency, Indonesia. It used a qualitative approach and the data were collected in several ways, i.e. focus group discussion, interview, secondary data, and observation. The study showed that village governments have no authority to design their own organizations, because the designs are prepared by central and local governments in detail. Moreover, lack of competence among village government staffs and financial dependency also make village governments rely on supports from central and local governments. It concludes that high intervene from upper governments make the village governments have limited room to manage their organizations. Secondly, policy disharmony among ministers also makes them in a dilemma about which one should be followed. Thirdly, various limited upon villages consequently makes them highly depend on supports, especially financial supports, from higher levels of government. Therefore, some actions need to be taken, such as reducing intervention, synchronizing policies among ministries, strengthening village organization and staffs, and optimizing the role of local government agency and stakeholders to take part in the village development process.